2012
DOI: 10.5144/0256-4947.2012.283
|View full text |Cite
|
Sign up to set email alerts
|

Profile of mycosis fungoides in 43 Saudi patients

Abstract: BACKGROUND AND OBJECTIVESMycosis fungoides (MF) is a rare disease; and to our knowledge, there are no reports on its profile in Arabs. The objective of this study was to preliminarily analyze the clinical characteristics of MF patients seen in our institution.DESIGN AND SETTINGRetrospective review of 140 patients with pathologic or clinical diagnosis or differential diagnosis of MF for the period 2000–2006.PATIENTS AND METHODSPathology reports with diagnosis or differential diagnosis of MF were retrieved and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
13
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
6
13
2
Order By: Relevance
“…Previous epidemiologic studies based on the Surveillance, Epidemiology and End Results (SEER) databases established that CTCL is on the rise in the United States and around the world . Similarly, a recent increase in these cancers has been identified in Saudi Arabia and Kuwait, where MF often affects children and adolescents . Our findings suggest that geographic mapping of patients by various CTCL centers will reveal additional areas of geographic clustering.…”
Section: Discussionsupporting
confidence: 52%
“…Previous epidemiologic studies based on the Surveillance, Epidemiology and End Results (SEER) databases established that CTCL is on the rise in the United States and around the world . Similarly, a recent increase in these cancers has been identified in Saudi Arabia and Kuwait, where MF often affects children and adolescents . Our findings suggest that geographic mapping of patients by various CTCL centers will reveal additional areas of geographic clustering.…”
Section: Discussionsupporting
confidence: 52%
“…The mean age of the HMF group (21.31 years) was close to that reported previously. 15,17,20 Although most of the encountered hypopigmented disorders in this study showed gradual onset, we found a progressive course, with increasing number of lesions, to be significantly associated with HMF, whereas a stationary course was significantly associated with postinflammatory hypopigmentation and small plaque parapsoriasis (hypopigmented type).…”
Section: Discussioncontrasting
confidence: 67%
“…In an Arab population, AlGhamdi et al described hypopigmented MF in 18 Saudi patients and they also observed a common affection of males (M : F ratio was 3.5 : 1), a younger age of onset (mean of 25 years) and mean duration of disease was 27.6 months. In Kuwait, Alsaleh et al reported a total number of 37 Arab patients with hypopigmented MF and they also observed a younger mean age at diagnosis (26.6 years) but without a significant difference from non‐Arab patients.…”
Section: Discussionmentioning
confidence: 98%